Sustainability of hospital-based midwife-led antenatal care consultation - a qualitative study - Anja Siegle; Friederike Zu Sayn-Wittgenstein; Martina Roes (BMC, 2021)
Abstract Background All evidence-based knowledge and improvement strategies for quality care must be implemented so patients can benefit from them. In Germany, national expert standards (NES) contribute to quality care in nursing and midwifery. The NES defines for several action levels a dedicated level of quality, which is operationalized by structure, process, and outcome (SPO) criteria. An NES to promote normal childbirth was developed and implemented in 2014. The first action level involves midwife-led antenatal consultation (ML-AC) being conducted in a structured way. Most implementation processes aim to accomplish sustainability, but implementation studies rarely use definitions or a theory of sustainability, even when assessing sustainability. This lack led to the assumption that intervention sustainability after implementation is still a largely unexplored domain. The aim of this study is to investigate the sustainability of midwife-led antenatal consultation (ML-AC) implemented at two hospitals, in Germany. Methods In a qualitative approach, 34 qualitative interviews were conducted (between March and October 2017) using semi-structured interview guides. All interviews were transcribed verbatim, anonymized and analyzed thematically using framework method. Four groups of stakeholders in two hospitals offering ML-AC were interviewed: managers (n = 8), midwives conducting ML-AC (n = 10), pregnant women who attended ML-AC (n = 8), and physicians working in obstetrics (n = 8) at the hospitals. Results The interviewees identified key benefits of ML-AC on a personal and unit level, e.g., reduced obstetric interventions, easier admission processes. Furthermore, the participants defined key requirements that are needed for routinized and institutionalized ML-AC, such as allocating working time for ML-AC, and structural organization of ML-AC. All study participants saw a need to establish secure long-term funding. Additionally, the interviewed staff members stated that ML-AC topics need evaluating and adapting in the future. Conclusions Implementing ML-AC in the hospital setting has led to manifold benefits. However, reimbursement through the health care system will be needed to sustain ML-AC. Hospitals implementing ML-AC will need to be aware that adaptations of the NES are necessary to accomplish routinization and institutionalization. After initial implementation, sustaining ML-AC will generally require on-going monitoring and evaluating of benefits, routinization/institutionalization and further development.